Farmer Characteristics' Effect on The Decision of Farmers in Choosing Local Variety Rice Farming Business - Meli Sasmi; Haris Susanto; Eldi Pama Kesamba Mula; Andi Alatas (Business Review and Case Studies, 2022)
Farmer characteristics are indicators that measure the ability of farmers to make decisions related to their farming activities. This study aims to determine the relationship between farmer characteristics and their decision to cultivate local varieties of lowland rice in Kuantan Singingi Regency. This research is survey research, the determination of samples from four sub-districts was selected purposively, each consisting of 15 farmers in each sub-district, the number of samples was 60 farmers. This study is a quantitative study using indicators and a measurement scale using the Likert Summated Branch (SLR) scale, with three categories of answers to the questions posed. The score expressed in integers (1,2,3) was then analyzed using a non-parametric analysis of Spearman's Rank Correlation using the SPSS-20 program. This finding shows that the number of family dependents has a significant relationship with farmers' decisions in farming local varieties of lowland rice and is negatively related, while the characteristics based on land area, farmer's age, education, and farming experience show a positive relationship but have no significant effect. Farmers who have some dependent families prefer to switch to planting high-yielding varieties to produce higher rice production and to meet the needs of family life. Based on the findings of this study, further research is needed on the potential development of local varieties of lowland rice as local superior varieties, taking into account aspects of land suitability, technology, and local wisdom. Keywords: farmers' decisions, characteristics, rice fields, local varieties, family dependents